BIBLIOMETRIC ANALYSIS OF YOUTH DEVELOPMENT POLICIES IN SPORTS IN BARRU REGENCY: CHALLENGES AND SUSTAINABILITY STRATEGIES - Jumria; Hj.Aidah (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal